Improvement of biogas production in plug flow reactor using biogas slurry pretreated cornstalk. (February 2020) - Dong, Lili; Cao, Guangli; Tian, Yushi; Wu, Jiwen; Zhou, Chunshuang; Liu, Bingfeng; Zhao, Lei; Fan, Jianing; Ren, Nanqi
Abstract: Biogas slurry pretreatment for enhancing the biomethanization of cornstalk was investigated. After pretreating 24 h with a volume proportion of biogas slurry and water of 4:1, the lignin reduction of cornstalk achieved 24.96%, while cellulose and hemicellulose decreased by 19.44%. Meanwhile, a large amount of volatile fatty acids were produced, which mainly composed of acetic acid. The fungi of Ascomycota and Neocallimastigomycota and bacteria of Bacteroidetes and Firmicutes cooperatively dominated the biogas slurry pretreatment. Subsequently, pretreated cornstalk was fermented in a semi-continuous anaerobic plug flow reactor for operated 120 d. The specific biogas and methane yield were up to 0.36 m 3 /kg VS and 0.21 m 3 /kg VS, respectively. The bacteria genera Clostridium III, Solibacillus, Sedimentibacter, Proteiniphilum, Petrimonas, Comamonas, and Ornatilinea were further enriched. Methanothrix and Methanobacterium became the dominant methanogen during the operation. These results provide an efficient and environmentally friendly approach for enhancing the lignocellulose to biogas. Highlights: Biogas slurry pretreatment for enhancing biomethanization of cornstalk was studied. After being pretreated 24 h, the lignin reduction achieved 24.96%. The specific methane yield was up to 0.21 m 3 /kg VS for pretreated cornstalk. This study provides a practical way for enhanced biogas production from cornstalk.